PENGARUH KINERJA KEUANGAN PEMERINTAH DAERAH DAN PENDAPATAN ASLI DAERAH TERHADAP INDEKS KEMANDIRIAN FISKAL DAERAH TAHUN 2016-2020 - Kiki Zakiah (Pusat Kajian Anggaran, 2022)
The purpose of this research is to analyze the effect of the Financial Performance of Local Government and Local Revenue (PAD) on the Regional Fiscal Autonomy Index. The research used secondary data from 501 provinces and municipalities/cities for the period of 2016-2020 from the Bureau Central of Statistics (BPS), Ministry of Finance, Supreme Audit Institution, and other related institutions. The research methodology used data panel regression. The results of the research show that the effectiveness of the regional budget variable has no effect on the regional fiscal autonomy index, and the efficiency of the regional budget variable and PAD have a positive and significant on the regional fiscal autonomy index.